The correlation between serum HBsAg levels and viral loads depends upon wild‐type and mutated HBV sequences rather than the HBeAg/anti‐HBe status. Issue 8 (16th April 2015) - Liu, Mo‐Han; Chen, Qin‐Yan; Harrison, Tim J.; Li, Guo‐Jian; Li, Hai; Wang, Xue‐Yan; Ju, Yu; Yang, Jin‐Ye; Fang, Zhong‐Liao
<x xml:space="preserve">Abstract</x> Despite several studies regarding the correlation between serum HBsAg titers and viral loads, the association remains uncertain. Eighty‐nine individuals were selected randomly from a Chinese cohort of 2, 258 subjects infected persistently with hepatitis B virus (HBV) for cross‐sectional and longitudinal analysis. Viral loads of mutant HBV are lower than those of wild type HBV. The serum HBsAg titers correlate positively with viral loads in both HBeAg positive and negative subjects (r = 0.449, P = 0.013; r = 0.300, P = 0.018, respectively). No correlation between serum HBsAg titer and viral loads was found in any of the four phases of chronic HBV infection. The serum HBsAg titers correlate positively with viral loads in the group with wild type sequences of the PreS/S, basal core promoter (BCP), and preC regions of HBV(r = 0.502, P = 0.040). However, the correlation was not seen in the group with mutations in these regions (r = 0.165, P = 0.257). The correlation between HBsAg titers and viral loads was seen in individuals with wild type PreS/S sequences but not in the subgroup with BCP double mutations or PreC stop mutation, although their sequences in the preS/S regions were wild type. All these findings were confirmed by the longitudinal analysis. In conclusion, the correlation between serum HBsAg levels and viral loads may not differ between HBeAg positive and negative individuals but may depend on wild‐type or mutated genomic sequences. Therefore, HBsAg quantitation may be used as a surrogate for viral loads in only wild‐type HBV infections. J. Med. Virol. 87:1351–1360, 2015. © 2015 Wiley Periodicals, Inc.